Factors Associated with Unsafe Actions by Brick Makers in Tanjung Mulia Village Pagar Merbau District Deli Serdang Regency - Sofia Diaz, Aya (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Brick maker is one of the informal sector industries that are mostly occupied by the people of Indonesia. Personal factors are one of the dominant factors influencing unsafe action, namely knowledge, training, workload and fatigue. This research is a quantitative study with an analytic observational study using a cross sectional study design. The purpose of this study is to explain the factors associated with unsafe action on brick makers in Tanjung Mulia Village, Pagar Merbau District in 2025. The number of samples was determined using simple random sampling method and obtained a sample of 53 workers. Data collection was carried out by interview using a questionnaire and observation sheet. The independent variables in this study are factors such as the level of knowledge, education and workload, while the dependent variable is unsafe action. The results showed that most brick makers experienced unsafe action with the category of lack of knowledge of 45 people (84.9%) and heavy workload category of 39 people (73.6%). There is a relationship between knowledge and unsafe action (p value = 0.002) and there is a relationship between workload and unsafe action (p value = 0.016). The conclusion of this study is that there is a relationship between the level of knowledge and workload with unsafe action. The advice that can be given is that every brick maker prioritizes safety and health while working in order to minimize unsafe action (unsafe action).